Pelayanan Akomodasi Vila di Pantai Tanjung Bayang Makassar - Mayasari, Mayasari; Ab., Ahmad; Renold, Renold (Journal of Hospitality Accommodation Management (JHAM), 2024)
This study aims to evaluate the cleanliness level and identify the facilities and services expected by guests at vila accommodations on Tanjung Bayang Beach, Makassar. The method used is a qualitative descriptive analysis with qualitative data collection techniques. The results show that cleanliness in the vilas needs to be improved to meet optimal standards. Recommendations include improving cleanliness in all vila areas and providing facilities that meet guests' expectations. The implementation of these findings is expected to increase guest satisfaction and the competitiveness of the vila accommodations